The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1371/journal.pone.0158669
|View full text |Cite
|
Sign up to set email alerts
|

Specific MAPK-Associated MicroRNAs in Serum Differentiate Pancreatic Cancer from Autoimmune Pancreatitis

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is difficult to distinguish from autoimmune pancreatitis (AIP) because of their clinical and radiological similarities, and therefore simple and minimally invasive surrogate markers for differential diagnosis would be useful. In our previous studies, we identified four microRNAs (miRNAs)–miR-7, miR-34a, miR-181d, and miR-193b –as MAPK-associated microRNAs whose expression was altered significantly with upregulation of the MAPK signaling pathway. Recently it has been repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Nonetheless, miRNAs exert vital roles in the occurrence and development of AP. A great deal of evidence has illustrated that miRNAs' primary function is to suppress the expression of downstream target genes by interacting with the 3'UTR of their mRNA [21][22][23], and therefore, miRNAs play critical regulatory roles in AP. It has been reported that miR-29 contributes to apoptosis in AR42J cells by targeting TNFRSF1A [24]; miR-22 and miR-135a promotes the apoptosis of pancreatic acinar cells in acute edematous pancreatitis through ErbB3 and Ptk2 [25]; miR-141 plays an important role in the regulation of autophagy in L-arginine-induced acute pancreatitis by targeting HMGB1 [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, miRNAs exert vital roles in the occurrence and development of AP. A great deal of evidence has illustrated that miRNAs' primary function is to suppress the expression of downstream target genes by interacting with the 3'UTR of their mRNA [21][22][23], and therefore, miRNAs play critical regulatory roles in AP. It has been reported that miR-29 contributes to apoptosis in AR42J cells by targeting TNFRSF1A [24]; miR-22 and miR-135a promotes the apoptosis of pancreatic acinar cells in acute edematous pancreatitis through ErbB3 and Ptk2 [25]; miR-141 plays an important role in the regulation of autophagy in L-arginine-induced acute pancreatitis by targeting HMGB1 [11].…”
Section: Discussionmentioning
confidence: 99%
“…And there was higher expression of miR-155 in tissues and synovial fibroblasts of patients with autoimmune disorders such as rheumatoid arthritis [38]. Actually, in the previous researches, they were focused on the correlation between higher expression of miR-155 and either chronic inflammation or autoimmune disorders in which it needed a relatively long time to maintain this state [14,22].…”
Section: Discussionmentioning
confidence: 99%
“…They not only provide for novel therapeutic options for pancreatic malignancy treatment, also the chance to aid in early diagnosis, disease monitoring and prognostic analysis[27, 29]. Recently, Manabu Akamatsu and his colleagues reported that four MAKP-associated miRNAs, miR-7, miR-34a, miR-181d, and miR-193b can be candidate biomarkers to differentiate pancreatic malignancy from AIP [30]. In this work, significantly higher amounts of serum miRNAs were detected in patients with pancreatic ductal adenocarcinoma (PDCA) than in those with AIP, and sensitivity of 72–79% together with specificity of 73–80% were obtained in ROC curve analysis [30].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Manabu Akamatsu and his colleagues reported that four MAKP-associated miRNAs, miR-7, miR-34a, miR-181d, and miR-193b can be candidate biomarkers to differentiate pancreatic malignancy from AIP [30]. In this work, significantly higher amounts of serum miRNAs were detected in patients with pancreatic ductal adenocarcinoma (PDCA) than in those with AIP, and sensitivity of 72–79% together with specificity of 73–80% were obtained in ROC curve analysis [30]. In recent work of Johansen and his colleagues, they analysed serum level of 34 miRNAs in patients with pancreatic cancer, chronic pancreatitis and healthy controls and developed a diagnostic panels based on 5 or 12 miRNAs (miR-16, -18a, -20a, -24, -25, -27a, -29c, -30a.5p, -191, -323.3p, -345 and miR-483.5p) to distinguish pancreatic cancer from pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…155 Furthermore, CpG methylation of miR-34a was also employed as a diagnostic indicator for the prognosis of patients with PC. 164 Akamatsu et al 165 found that the expression level of miR-34a in serum could be used as a biomarker to distinguish between PDAC and autoimmune pancreatitis (AIP). These studies indicate that miR-34a and its methylation levels may be used as indicators for diagnosis and prognosis in patients with PC.…”
Section: The Role Of Mir-34a In the Diagnosis And Prognosis Of Pcmentioning
confidence: 99%